Enzymatic synthesis of biphenyl-DNA oligonucleotides. Issue 11 (1st June 2020) - Röthlisberger, Pascal; Levi-Acobas, Fabienne; Leumann, Christian J.; Hollenstein, Marcel
Graphical abstract: Highlights: Synthesis of biphenyl-modified nucleoside triphosphate. Stereoelectronic environment of distal ring in template influences incorporation. Two-step protocol for enzymatic synthesis of oligonucleotides containing C -nucleotides. TdT-mediated tailing reactions. Abstract: The incorporation of nucleotides equipped with C -glycosidic aromatic nucleobases into DNA and RNA is an alluring strategy for a number of practical applications including fluorescent labelling of oligonucleotides, expansion of the genetic alphabet for the generation of aptamers and semi-synthetic organisms, or the modulation of excess electron transfer within DNA. However, the generation of C-nucleoside containing oligonucleotides relies mainly on solid-phase synthesis which is quite labor intensive and restricted to short sequences. Here, we explore the possibility of constructing biphenyl-modified DNA sequences using enzymatic synthesis. The presence of multiple biphenyl-units or biphenyl residues modified with electron donors and acceptors permits the incorporation of a single dBphMP nucleotide. Moreover, templates with multiple abasic sites enable the incorporation of up to two dBphMP nucleotides, while TdT-mediated tailing reactions produce single-stranded DNA oligonucleotides with four biphenyl residues appended at the 3′-end.